Evolution of Substance use, Neurological and Psychiatric Symptoms in Schizophrenia and Substance use Disorder Patients: A 12-Week, Pilot, Case–Control Trial with Quetiapine - Zhornitsky, Simon; Stip, Emmanuel; Desfosses, Joelle; Pampoulova, Tania; Rizkallah, Elie; Rompre, Pierre-Paul; Bentaleb, Lahcen A.; Lipp, Olivier; Chiasson, Jean-Pierre; Gendron, Alain; Potvin, Stephane (Frontiers in Psychiatry, 2011)
Neurological and psychiatric symptoms are consequences of substance abuse in schizophrenia and non-schizophrenia patients. The present case-control study examined changes in substance abuse/dependence and neurological and psychiatric symptoms in substance abusers with (DD group, n=26) and without schizophrenia (SUD group, n=24) and in non-abusing schizophrenia patients (SCZ group, n=23) undergoing 12-week treatment with the atypical antipsychotic, quetiapine. Neurological and psychiatric symptoms were evaluated with the Positive and Negative Syndrome Scale, the Calgary Depression Scale for Schizophrenia, the Extrapyramidal Symptoms Rating Scale and the Barnes Akathisia Rating Scale. At endpoint, DD and SCZ patients were receiving significantly higher doses of quetiapine (mean = 554mg/d and 478mg/d, respectively), relative to SUD patients (mean = 150mg/d). We found that SUD patients showed greater improvement in weekly dollars spent on alcohol and drugs and SUD severity, compared to DD patients. At endpoint, there was no significant difference in dollars spent, but DD patients still had a higher mean SUD severity. Interestingly, DD patients had significantly higher Parkinsonism and depression than SCZ patients at baseline and endpoint. On the other hand, we found that SUD patients had significantly more akathisia at baseline, improved more than SCZ patients and this was related to cannabis abuse/dependence. Finally, SUD patients improved more in PANSS positive scores than DD and SCZ patients. Taken together, our results provide evidence for increased vulnerability to the adverse effects of alcohol and drugs in schizophrenia patients. They also suggest that substance abuse/withdrawal may mimic some symptoms of schizophrenia. Future studies will need to determine the role quetiapine played in these improvements.